Comparison of the investigational device exemption and post‐approval trials of the Melody transcatheter pulmonary valve. Issue 2 (29th March 2021) - Kreutzer, Jacqueline; Armstrong, Aimee K.; Rome, Jonathan J.; Zellers, Thomas M.; Balzer, David T.; Zampi, Jeffrey D.; Cabalka, Allison K.; Javois, Alexander J.; Turner, Daniel R.; Gray, Robert G.; Moore, John W.; Weng, Shicheng; et al.
Abstract: Objective: We compared 5‐year outcomes of transcatheter pulmonary valve (TPV) replacement with the Melody TPV in the post‐approval study (PAS) and the investigational device exemption (IDE) trial. Background: As a condition of approval of the Melody TPV after the IDE trial, the Food and Drug Administration required that a PAS be conducted to evaluate outcomes of TPV replacement in a "real‐world" environment. The 5‐year outcomes of the PAS have not been published, and the IDE and PAS trials have not been compared. Methods: The cohorts comprised all patients catheterized and implanted at 5 IDE sites and 10 PAS sites. Differences in trial protocols were detailed. Time‐related outcomes and valve‐related adverse events were compared between the two trials with Kaplan–Meier curves and log‐rank testing. Results: 167 patients (median age, 19 years) were catheterized and 150 underwent TPV replacement in the IDE trial; 121 were catheterized (median age, 17 years) and 100 implanted in the PAS. Freedom from hemodynamic dysfunction ( p = .61) or any reintervention ( p = .74) over time did not differ between trials. Freedom from stent fracture ( p = .003) and transcatheter reintervention ( p = .010) were longer in PAS, whereas freedom from explant ( p = .020) and TPV endocarditis ( p = .007) were shorter. Clinically important adverse events (AEs) were reported in 14% of PAS and 7.2% of IDE patients ( p = .056); the incidence of any particular event was low in both. Conclusions: Hemodynamic and time‐related outcomes in the PAS and IDE trials were generally similar, confirming the effectiveness of the Melody TPV with real‐world providers. There were few significant complications and limited power to identify important differences in AEs. The lack of major differences in outcomes between the two studies questions the usefulness of mandated costly post‐approval studies as part of the regulatory process for Class III medical devices.